2017
DOI: 10.1063/1.4978855
|View full text |Cite
|
Sign up to set email alerts
|

150 mW deep-ultraviolet light-emitting diodes with large-area AlN nanophotonic light-extraction structure emitting at 265 nm

Abstract: High-power 265 nm deep-ultraviolet (DUV) AlGaN-based light-emitting diodes (LEDs) with large-area AlN nanophotonic light-extraction structures that were fabricated by a nanoimprint lithography process are presented. Each DUV-LED has a large active area (mesa size of ∼0.35 mm2) and a uniform current spreading design that allows high injection current operation. We have shown that these DUV-LEDs with their large-area nanoimprinted AlN nanophotonic structures exhibit wider near-field emitting areas, stronger far-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
122
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(123 citation statements)
references
References 18 publications
1
122
0
Order By: Relevance
“…A maximum light extraction enhancement of 196% was obtained in 265-nm LEDs with the hybrid structure in comparison to that of a flat surface device. To enable high-output and high-volume fabrication, they further presented 265-nm DUV LEDs with largearea nanoimprinted AlN nanophotonic structures, 7 which showed wider near-field emitting areas, stronger far-field extracted light intensities, and an approximately 20-fold increase in LOP compared with a conventional flat-surface LED.…”
Section: Substrate Surface Rougheningmentioning
confidence: 99%
See 1 more Smart Citation
“…A maximum light extraction enhancement of 196% was obtained in 265-nm LEDs with the hybrid structure in comparison to that of a flat surface device. To enable high-output and high-volume fabrication, they further presented 265-nm DUV LEDs with largearea nanoimprinted AlN nanophotonic structures, 7 which showed wider near-field emitting areas, stronger far-field extracted light intensities, and an approximately 20-fold increase in LOP compared with a conventional flat-surface LED.…”
Section: Substrate Surface Rougheningmentioning
confidence: 99%
“…[2][3][4][5] Recently, Takano et al 6 claimed to obtain deep-UV (DUV) LEDs with a maximum external quantum efficiency (EQE) of 20.3% at 275 nm. Inoue et al 7 reported a 265-nm single-chip LED with a record continuous-wave output power in excess of 150 mW (corresponding EQE: 3.9%) for an injection current of 850 mA. However, the typical EQE of DUV LEDs is still in the single-digit percentage range and the output power in a couple of milliwatts, depending on the wavelength.…”
Section: Introductionmentioning
confidence: 99%
“…DUV LEDs generally employ flip-chip configuration for efficient heat dissipation and light extraction [21][22][23][24]. In spite of this, flip-chip designs still suffer from a relatively low extraction efficiency caused by the dominant transverse magnetic (TM)-polarized light emission, which propagates mainly in the lateral direction [25].…”
Section: Device Design For Improved Performance Of Group Iii-nitride mentioning
confidence: 99%
“…The 255 nm DUV LEDs with a sapphire lens fabricated using the surface activated bonding method have shown a light extraction efficiency enhancement of 2.8 times when compared to a reference LED lacking the lens, and an EQE of 4.56% was achieved. Inoue et al [5,24] have developed large-area AlN nanophotonic structures to enhance the light extraction efficiency of DUV LEDs. The LEDs with the nanoimprinted AlN nanophotonic structures exhibit wider near-field emitting areas, stronger far-field extracted light intensities, and an approximately 20-fold increase in the output power when compared with a conventional flat-surface DUV LED.…”
Section: Device Design For Improved Performance Of Group Iii-nitrde Dmentioning
confidence: 99%
“…A CW output power in excess of 150 mW for an injection current of 850 mA has been achieved in the nanoimprinted UVC LEDs emitting at 265 nm. [24] Nagai et al [25][26][27] have investigated the feasibility of encapsulation of AlGaN-based DUV LEDs with silicone resin and with polymerized perfluoro-4-vinyloxy-1-butene (BVE)-based fluorine polymers having -COOCH3 ends in comparison with fluorine polymers having terminal ends of -CF3 and -COOH in order to enhance light extraction. Serious damage to the electrode metal was observed, except for the BVE-based polymer with -CF3 ends.…”
Section: Device Design For Improved Performance Of Group Iii-nitrde Dmentioning
confidence: 99%